2021
DOI: 10.1161/circheartfailure.121.008406
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Heart Failure Among Urban Patients in China: A National Population-Based Analysis

Abstract: Background: Large-scale and population-based studies of heart failure (HF) incidence and prevalence are scarce in China. The study sought to estimate the prevalence, incidence, and cost of HF in China. Methods: We conducted a population-based study using records of 50.0 million individuals ≥25 years old from the national urban employee basic medical insurance from 6 provinces in China in 2017. Incident cases were individuals with a diagnosis of HF (Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(91 citation statements)
references
References 35 publications
1
90
0
Order By: Relevance
“…The transition probability for CHD, death, and in-hospital death was 0.0854, 1.0763, and 2.5665%, respectively. Using the same formula, we could draw that the transition probabilities for HF and stroke were 0.0229 and 0.0288%, and the transition probabilities for death and inhospital death for HF and stroke were 0.5368 vs. 0.8632% and 2.7683 vs. 1.5447% (Table 1) (20,21,23).…”
Section: Parameter Input Transition Probability Inputmentioning
confidence: 96%
“…The transition probability for CHD, death, and in-hospital death was 0.0854, 1.0763, and 2.5665%, respectively. Using the same formula, we could draw that the transition probabilities for HF and stroke were 0.0229 and 0.0288%, and the transition probabilities for death and inhospital death for HF and stroke were 0.5368 vs. 0.8632% and 2.7683 vs. 1.5447% (Table 1) (20,21,23).…”
Section: Parameter Input Transition Probability Inputmentioning
confidence: 96%
“…Studies reported that approximately 12 million Chinese adults suffered from HF and estimated that the prevalence of HF would keep rising ( Wang, 2017 ; Hao et al, 2019 ). In 2017, the estimated average annual hospitalization cost for HF was $4,406.8 per patient, and the cost of all drugs accounted for 30.6% of the total medical expenses ( Wang et al, 2021 ). In recent years, several studies have proved the effectiveness of sodium-glucose cotransporter-2 (SGLT2) inhibitors in the treatment of patients with HF.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports have emphasized that heart failure (HF) is a major global health problem, in that the overall number of people including older adults with HF has increased due to considerable increases in predisposing diseases or comorbidities [ 1 , 2 , 3 ]. Likewise, the incidence of patients with HF in South Korea was estimated to be 1.53% in 2013 and is expected to increase by 2.2-fold to 3.4% by 2040 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%